Brazilian society and regional integration - Alimonda, Hector (2000)
Focuses on the theme of MERCOSUR and democracy in Brazil. Summarizes the experiences of popular actors seeking a more democratic pattern of procedures and the identification of social justice and welfare politics as the core of the process of regional integration.